Synthesis and characterization of a magnetic bacterial cellulose-chitosan nanocomposite and evaluation of its applicability for osteogenesis - Nahid Rezazadeh; Effat Alizadeh; Somaieh Soltani; Soodabeh Davaran; Neda Esfandiari (BioImpacts)
Introduction: Natural biopolymers are used for various purposes in healthcare, such as tissue engineering, drug delivery, and wound healing. Bacterial cellulose and chitosan were preferred in this study due to their non-cytotoxic, biodegradable, biocompatible, and non-inflammatory properties. The study reports the development of a magnetic bacterial cellulose-chitosan (BC-CS-Fe3O4) nanocomposite that can be used as a biocompatible scaffold for tissue engineering. Iron oxide nanoparticles were included in the composite to provide superparamagnetic properties that are useful in a variety of applications, including osteogenic differentiation, magnetic imaging, drug delivery, and thermal induction for cancer treatment. Methods: The magnetic nanocomposite was prepared by immersing Fe3O4 in a mixture of bacterial cellulose-chitosan scaffold and then freeze-drying it. The resulting nanocomposite was characterized using FE-SEM and FTIR techniques. The swelling ratio and mechanical strength of the scaffolds were evaluated experimentally. The biodegradability of the scaffolds was assessed using PBS for 8 weeks at 37°C. The cytotoxicity and osteogenic differentiation of the nanocomposite were studied using human adipose-derived mesenchymal stem cells (ADSCs) and alizarin red staining. One-way ANOVA with Tukey's multiple comparisons test was used for statistical analysis. Results: The FTIR spectra demonstrated the formation of bonds between functional groups of nanoparticles. FE-SEM images showed the integrity of the fibrillar network. The magnetic nanocomposite has the highest swelling ratio (2445% ± 23.34) and tensile strength (5.08 MPa). After 8 weeks, the biodegradation ratios of BC, BC-CS, and BC-CS-Fe3O4 scaffolds were 0.75% ± 0.35, 2.5% ± 0.1, and 9.5% ± 0.7, respectively. Magnetic nanocomposites have low toxicity (P < 0.0001) and higher osteogenic potential compared to other scaffolds. Conclusion: Based on its high tensile strength, low water absorption, suitable degradability, low cytotoxicity, and high ability to induce an increase in calcium deposits by stem cells, the magnetic BC-CS-Fe3O4 nanocomposite scaffold can be a suitable candidate as a biomaterial for osteogenic differentiation.